Double uncrossed patellar tendon: a rare knee variant case series - Adil Basha; Ali Shaikh; Flavio Duarte Silva; Subba Rao Chaganti; Avneesh Chhabra (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background The double uncrossed patellar tendon is a rare anatomical variant of the patellar tendon. This case report serves to underscore the importance of recognizing the double uncrossed patellar tendon variant, as it can mimic other knee pathologies, leading to potential misdiagnosis and unnecessary interventions. Case presentation We report three cases of the uncrossed double patellar tendon encountered on knee MRIs in the last 12 months. All three cases were confirmed to be incidental findings in patients with underlying knee complaints, for which they underwent conservative and interventional treatments and had near complete to complete recoveries. Conclusion The presence of the double patellar tendon did not have an identifiable detrimental effect in the cases of interest, but we believe more research is needed to further understand the clinical implications and prevalence of this anatomical anomaly to help in differentiating between congenital findings and acquired patellar tendon pathologies.